(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2026)
Congenital abnormalities of the facial jaw in children are considered one of the most important craniofascial pathologies found among children and adolescents. Cleft palate and palate, facial skeletal deformities, prikus disorders, chemtics in the upper lip and alveolar tumor are not only an aesthetic defect, but also seriously impair nutrition, swallowing, sucking, speech and psychoemotional development. According to world literature, lip or palate kemtics can correspond to 1:700-1:1000 newborn children, while in some regions it is noted that this figure is even higher. In different regions, environmental factors, reproductive age of the parent, genetic factors, medications and harmful habits that the mother took during pregnancy (smoking, alcohol) can affect the frequency of occurrence of these pathologies. In the Khorezm region, the high proportion of rural residents, the health of women of reproductive age, the different levels of the quality of prenatal observation, the inhomogeneity of perinatal care can be considered as factors affecting the number of children with congenital anomalies of the facial jaw and their functional state [1.3.5.7.9.11.13.15]. At the same time, complex rehabilitation in these patients – surgical, orthodontic, logopedic and psychosocial support – is required for several years at a minimum.